Demonstrações em geometria no ensino médio: uma proposta de atividades para se trabalhar de forma remota - Camara, Luciano Tavares (2021)
Mathematical proofs develop in students the ability to argue, question, raise hypotheses and solve problems. The benefits achieved when working with proofs go far beyond the acquisition of mathematical knowledge. These skills, once acquired, are carried throughout life, providing the formation of critical citizens who knows how to position themselves before society. Therefore, this work aims to propose activities that exercise the students deductive sense and arouse in them the curiosity for mathematical knowledge culminating in proofs of some important theorems of geometry. Such activities were designed the teacher can develop them remotely with high school students.